Thermodynamic tuning of lithium borohydride using various metallic sources - Deavin, Oliver (2018)
Lithium borohydride (LiBH4) has been shown great interest as a hydrogen storage material owing to its large hydrogen storage capacity of 18.5 wt%, but unfortunately to release the vast majority of the stored hydrogen requires temperatures in excess of 600 °c. To improve the temperature at which LiBH4 decomposes, and to improve its poor reversibility, a process known as thermodynamic tuning can be used. Thermodynamic tuning involves creating new, more favourable reaction pathways and in this work the addition of nickel, silicon, iron and cobalt were investigated.